Nursing Intervention for Outpatient Rehabilitation in Pediatric Patients with Hirschsprung Disease after Colectomy - Wang, Hui; Guo, Xia-Ne; Zhu, Dan; Zhu, Tianqi; Hu, Lu-Hong; Feng, Jie-Xiong (European Journal of Pediatric Surgery, 2015)
Objective The present study was designed to evaluate the effectiveness of a nursing intervention program for outpatient rehabilitation of children with Hirschsprung-associated enterocolitis (HAEC) after radical colectomy for Hirschsprung disease (HD).Background Postoperative outcomes severely affect the quality of life in pediatric HD patients after operation. The improvement in defecation function is regarded as one of the most useful parameters to evaluate the quality of life in HD patients after radical intestinal resection. A close attention should also be paid to the patients' ability of social adaptation.Methods This prospective, randomized control trial enrolled 85 pediatric patients with HAEC after colectomy. They were randomly divided into the control and intervention groups. All the patients were followed up for 6 to 12 months after initial HAEC treatment.Results The intervention group had a lower enterocolitis recurrence rate than the control group, with a better ability to control defecation and their parents had better rehabilitation nursing knowledge (p < 0.05). The degree of parents' satisfaction regarding the outcome was significantly better in the intervention group than that in the control group (p < 0.05).Conclusion A systemic rehabilitation nursing program could decrease enterocolitis recurrence, improve the recovery of anorectal functions, and enhance the quality of life in the pediatric patients after radical colectomy.
Keywords: Hirschsprung disease; enterocolitis; rehabilitation nursing intervention; quality of life; colectomy